The Customer Foresight Territory - Eric Eller; Rupert Hofmann; Jan Oliver Schwarz (Marketing Review St.Gallen, 2020)
Customer foresight is a relatively new research field. We introduce the customer foresight territory by discussing its localization between customer research and foresight research. For this purpose, we look at a variety of methods that help to understand customers and future realities. On this basis we provide an overview of customer foresight methods and outline an ideal-typical research journey.
Keywords: 650